Biennial Report on Operations Evaluation in IFC 2008 : Enhancing Monitoring and Evaluation for Better Results - World Bank (World Bank, Washington, DC, 2012)
The Biennial Report on Operations Evaluation (BROE) in International Finance Corporation (IFC) assesses the adequacy, coverage, and quality of monitoring and evaluation (M&E) in IFC and makes recommendations for improvements going forward. It covers IFC management's M&E of its performance and also IEG's independent evaluation activities. In the last three years, IFC has made advances in monitoring and evaluating its performance: (i) new M&E tools have been introduced to cover all active investments and advisory services operations; and (ii) the use of M&E results in informing IFC strategy and in linking incentives to project results has grown. The report recommends that IFC management and Independent Evaluation Group (IEG) develop more robust and consistent metrics for monitoring and assessing IFC's additionality and development impact at the sector and country levels, as IFC transitions to a more programmatic approach in its interventions.